2010
DOI: 10.1007/s10562-010-0347-7
|View full text |Cite
|
Sign up to set email alerts
|

Gallium(III) Triflate Catalyzed Direct Reductive Amination of Aldehydes

Abstract: Direct hydroamination of aldehydes and ketones provides one-step entry into desired a-aminoalkane derivatives which are important synthons for many biologically active molecules. The reductive amination of aldehydes in the presence of silanes has been effectively promoted by Ga(OTf) 3 as a catalyst. Mild conditions, easy work-up and high purity of products with excellent yields are the major advantages of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…249.7°C) obtained by the reductive amination of triacetoneamine (TAA) and n-butylamine is a key intermediate of hindered amine light stabilizers (HALS), which have dominated light stabilizers market for several decades due to their excellent light stabilization [1,2]. It is well known that reductive amination of carbonyl compounds is an important method for the production of amines [3][4][5]. Up to now, the reductive amination of TAA with n-butylamine to TEMPBA in autoclave has been widely described in many studies in the presence of cobalt, nickel, platinum or palladium as catalysts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…249.7°C) obtained by the reductive amination of triacetoneamine (TAA) and n-butylamine is a key intermediate of hindered amine light stabilizers (HALS), which have dominated light stabilizers market for several decades due to their excellent light stabilization [1,2]. It is well known that reductive amination of carbonyl compounds is an important method for the production of amines [3][4][5]. Up to now, the reductive amination of TAA with n-butylamine to TEMPBA in autoclave has been widely described in many studies in the presence of cobalt, nickel, platinum or palladium as catalysts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we have shown that gallium (III) trifluoromethanesulfonate [Ga(OTf) 3 , gallium triflate], acts as an effective but mild and water tolerant Lewis acid catalyst for many organic synthetic transformations such as Friedel-Crafts alkylations, dehydration of oximes to the corresponding nitriles, Beckman rearrangement, etc. [44][45][46][47][48][49][50][51][52]. We also found that gallium triflate offers the optimum acidity required for ketonic Strecker reaction [53] and the synthesis of various heterocycles such as dihydrobenzimidazolines, benzothiazolines, benzoxazinones etc.…”
Section: Introductionmentioning
confidence: 68%
“…Our recent studies involving reductive amination of aldehydes showed that Ga(OTf) 3 acts as an aqueous-stable catalyst for the activation of various silane reducing agents [52]. In the present method, the carbonyl reduction of a variety of ketones to the corresponding methylenic products has been efficiently carried out in a similar fashion under mild conditions (Scheme 1).…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the high-yield synthesis of quinoxalines and 1,5-benzodiazepines by condensation of 1,2-diaminoaryls with 1,2-and 1,3-diketones in the presence of a catalytic amount of Ga(OTf) 3 (5 mol%) represents an important contribution (22 Hydroamination of Aldehydes The efficient synthesis of aryl benzyl amines bearing various functional groups was achieved via a one-pot, three-component (aldehyde, aryl amine, organosilane) reaction catalyzed by Ga(OTf) 3 (5 mol%, 24). 30 It was suggested that the reaction involves silane addition to a Ga(OTf) 3 …”
Section: Direct Substitution Of Alcohols With Sulfur Nucleophilesmentioning
confidence: 99%
“…The salt [(IDipp)GaCl 2 ][SbF 6 ] (IDipp = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene) displayed the highest activity (30). 42, 43 However, the latter is moisture sensitive and in situ generation of the active cationic species is preferred.…”
Section: N-heterocyclic Carbene (Nhc) Ligandsmentioning
confidence: 99%